Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Tailoring oxygen vacancy-rich NH4V4O10/porous carbon hierarchical structures for superior aqueous zinc-ion batteries - Yong Liao; Dui Ma; Qifan You; Hongtao Zhang; Jiaming Ni; Zhiqiang Xiong; Xiao Liang; Haitao Huang (Chemical Engineering Journal, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Response of bacterial pathogens to process upgrades and floc sizes in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Haipeng Zhang; Rongxin Zhang (Journal of Environmental Management, 2025)

Parallel algorithm of watershed delineation by considering the topological relationship into information organisation - Fei Zhao; Liyang Xiong; Hongen Wang; Lanhua Luo; Jiaming Na; Sijin Li; Guoan Tang (Environmental Modelling & Software, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

Rheological and thermal property of KH570-modified nano-SiO2 grafted xanthan gum and its application in drilling fluid system - Jingqi Shi; Long Chen; Ruihan Xie; Jiayin Zhang; Shuangcheng Pi; Jiaming Yang; Yunhai Zhao; Feng Xiong; Yongkui Zhang; Tonghui Xie (Carbohydrate Polymers, 2025)

Cell wall and reactive oxygen metabolism responses of stored Shine Muscat grapes to combined melatonin and 24-epibrassinolide treatment - Yaoying Zeng; Jiaming Zhang; Hui Su; Le Xie; Ye Zhao; Yubo Xiong; Zhou Wenhua (Postharvest Biology and Technology, 2025)

Microbial community dynamics in different floc size aggregates during nitrogen removal process upgrading in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Rongxin Zhang (Bioresource Technology, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Kinematic Stability Analysis of Anchor Cable Structures in Submerged Floating Tunnel under Combined Parametric–Vortex Excitation - Jiaming Xiong; Song Sang; Youwei Du; Chaojie Gan; Ao Zhang; Fugang Liu (Journal of Marine Science and Engineering, 2024)
The submerged floating tunnel is a marine transportation infrastructure that links two shorelines. The tunnel tube body’s buoyancy exceeds gravity, with anchoring ensuring equilibrium. Anchoring reliability is crucial. This study presents a three-way coupled kinematic model for the mooring structure, formulated on Hamilton’s principle and Kirchhoff’s assumption. It explores the impact of the tube body’s buoyancy-to-weight ratio and the sea current’s angle of incidence on mooring motion response. By solving the motion analysis model, Hill’s equation system is derived to assess the parameter instability of the anchor cable structure. The coefficient of excitation instability intervals for the submerged floating tunnel is determined and validated. The findings indicate the following: (1) Increasing the float-weight ratio reduces displacement response amplitudes in all directions, bringing downstream and transverse currents closer to their initial positions; (2) Changes in current direction angles result in decreased downstream excitation strength and increased transverse displacement response with the same excitation direction; (3) The instability interval visualization effectively predicts anchor cable structure instability under parametric excitation. Structures within the instability region are deemed unstable, while those outside are considered stable.

Informer-Based Model for Long-Term Ship Trajectory Prediction - Caiquan Xiong; Hao Shi; Jiaming Li; Xinyun Wu; Rong Gao (Journal of Marine Science and Engineering, 2024)
Ship trajectory prediction is a complex time series forecasting problem that necessitates models capable of accurately capturing both long-term trends and short-term fluctuations in vessel movements. While existing deep learning models excel in short-term predictions, they struggle with long-sequence time series forecasting (LSTF) due to difficulties in capturing long-term dependencies, resulting in significant prediction errors. This paper proposes the Informer-TP method, leveraging Automatic Identification System (AIS) data and based on the Informer model, to enhance the ability to capture long-term dependencies, thereby improving the accuracy of long-term ship trajectory predictions. Firstly, AIS data are preprocessed and divided into trajectory segments. Secondly, the time series is separated from the trajectory data in each segment and input into the model. The Informer model is utilized to improve long-term ship trajectory prediction ability, and the output mechanism is adjusted to enable predictions for each segment. Finally, the proposed model’s effectiveness is validated through comparisons with baseline models, and the influence of various sequence lengths Ltoken on the Informer-TP model is explored. Experimental results show that compared with other models, the proposed model exhibits the lowest Mean Squared Error, Mean Absolute Error, and Haversine distance in long-term forecasting, demonstrating that the model can effectively capture long-term dependencies in the trajectories, thereby improving the accuracy of long-term vessel trajectory predictions. This provides an effective and feasible method for ensuring ship navigation safety and advancing intelligent shipping.

Effect of Stratified Flow on the Vibration of Anchor Cables in a Submerged Floating Tunnel - Jiaming Xiong; Song Sang; Xiao Shi; Chaojie Gan (Journal of Marine Science and Engineering, 2024)
This study investigates the vertical-type submerged floating tunnel with anchor cables. Based on the characteristics of the anchor cables, the anchor cables are simplified as a nonlinear beam model with hinged ends. Disregarding the axial displacement of the tunnel body, the loads will cause displacements in the x and z directions of the tunnel body. The vibrations of the anchor cables are decomposed into three directions, and the parameter excitation at the connection point between the anchor cables and the tunnel body is taken into account. The equations of motion for the three degrees of freedom of the anchor cables are established using Hamilton’s principle, and then the three equations are solved using the Galerkin method and the fourth-order Runge–Kutta method. The basic characteristics of an internal wave stratified flow acting on the anchor cables are considered, as well as the influence of the incident angle of the ocean currents on the three degrees of freedom of the anchor cables. The results indicate that (1) stratified flow weakens the first- and third-order vortex-induced vibrations of the anchor cables while enhancing the second-order vortex-induced vibrations. When considering the parameter excitation of the anchor cables, the first- and third-order vibrations are weakened, while the second-order vibration remains significant; (2) the first-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency, and the second-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency; (3) the downstream vibration of the anchor cables increases with the increase in the incident angle of the ocean currents, the cross-flow vibration of the anchor cables decreases with the increase in the incident angle of the ocean currents, and the axial vibration of the anchor cables reaches its maximum value when the incident angle of the ocean currents is 60 degrees; (4) stratified flow weakens the lock-in phenomenon of the anchor cables, and the influence of the 1/2 stratified flow on the vibrations of the anchor cables is greater than the influence of the 1/2 stratified flow.

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Regional Modeling of the Lithospheric Magnetic Field from Local and Satellite Constraints: A Case Study of the Xinjiang Region - Yan Feng; Jiaxuan Zhang; Shengqing Xiong; JinYuan Zhang; Jiaming Ou; Shuang Liu; Yijun Li; Ya Huang (Pure and Applied Geophysics, 2023)

Thermal-and-mechanochemical recycling of waste polypropylene into maleated-epoxided degradation products as warm-mix asphalt modifier: Performance improvement and production mechanism analysis - Xiong Xu; Yaming Chu; Yi Luo; Yuhao Peng; Nannan Yang; Jiaming Yan; Xuyong Chen; Fuliao Zou; Anand Sreeram (Journal of Cleaner Production, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Dynamic retention of thallium(I) on humic acid: Novel insights into the heterogeneous complexation ability and responsiveness - Wanpeng Chen; Xiaoliu Huangfu; Jiaming Xiong; Hongxia Liu; Qiang He (Water Research, 2023)

Experimental investigation on pressure oscillation induced by steam injection into subcooled water through an opposite nozzle - Haitao Ren; Dingding Liang; Tao Lu; Jie Wang; Pei Yu; Jie Li; Jiaming Zhao; Ping Xiong (Annals of Nuclear Energy, 2023)

Adaptive neighbourhood recovery method for machine learning based 3D point cloud classification - Jiaming Xue; Chaoguang Men; Yongmei Liu; Shun Xiong (International Journal of Remote Sensing, 2023)

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Chlorine dioxide bleaching wastewater degradation in intimately coupled photocatalysis and functional bacteria: The roles of adsorption, photocatalysis, and biotransformation - Yinna Liang; Maman Galandi Abdoulaye; Chenxu Zhou; Bing Xiao; Jiaming Zhang; Jianhua Xiong; Qifeng Yang; J.R. Zhao; Shuangfei Wang (Journal of Cleaner Production, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Scientific attributes and expression methods of geographical boundary - Guoan Tang; Jilong Li; Liyang Xiong; Jiaming Na (Journal of Geographical Sciences, 2022)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

Dynamic mathematical models of batch experiments and fed-batch cultures for cyclic adenosine monophosphate production by Arthrobacter A302 - Lei Li; Xiaochun Chen; Huajing Ren; Jiaming Cao; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2011)